MS EXCEL PROGRAMMASÍNDA “ELEKTRON KLASS JURNAL” JARATÍW METODIKASÍ - Abdullaev, A.; Raxmetova, L. (ILIM hám JÁMIYET, 2019)
The article deals with the description of working out the method of using the "Electronic class journal" algorithm in MS Excel and its use in the teaching process.